Best Maritime Policy & Management paper for 2019 award - Zis, Thalis (My University, 2026)
The second major output of the RoRoSECA project, was published in 2019 at the MPM journal (co-authored with Psaraftis). This journal has a high impact factor compared to other journals focusing on maritime logistics, and is a key outlet for papers related in this field. In 2020, my paper was selected as the best journal paper published (in print) during 2019, out of a total of 55 papers that were also eligible for this award. This research (RoRoSECA project) was co-funded by the DMF and Orients Fund, and thus this is an important highlight for the two Danish funding bodies, and the research these have funded.
Keywords: Sciences